2011
DOI: 10.1128/mcb.01305-10
|View full text |Cite
|
Sign up to set email alerts
|

A Runx1-Smad6 Rheostat Controls Runx1 Activity during Embryonic Hematopoiesis

Abstract: The oncogenic transcription factor Runx1 is required for the specification of definitive hematopoietic stem cells (HSC) in the developing embryo. The activity of this master regulator is tightly controlled during development. The transcription factors that upregulate the expression of Runx1 also upregulate the expression of Smad6, the inhibitory Smad, which controls Runx1 activity by targeting it to the proteasome. Here we show that Runx1, in conjunction with Fli1, Gata2, and Scl, directly regulates the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
1
19
0
4
Order By: Relevance
“…RUNX1 can also modulate its own level by upregulating the expression of Smad6 to target itself for proteasome degradation [44]. It was found that RUNX1, but not its mutants, synergistically activated the PF4 promoter in combination with ETS-1 and CBFβ, or FLI-1 [45]. And RUNX1 was also reported to modulate the fate of hematopoietic cells achieved by binding to the thrombopoietin (TPO) recaptor/c-Mpl promoter, followed by the recruitment of transcription activators or repressors in order to promote transition of the hemogenic endothelium to HSCs [42,46].…”
Section: Discussionmentioning
confidence: 99%
“…RUNX1 can also modulate its own level by upregulating the expression of Smad6 to target itself for proteasome degradation [44]. It was found that RUNX1, but not its mutants, synergistically activated the PF4 promoter in combination with ETS-1 and CBFβ, or FLI-1 [45]. And RUNX1 was also reported to modulate the fate of hematopoietic cells achieved by binding to the thrombopoietin (TPO) recaptor/c-Mpl promoter, followed by the recruitment of transcription activators or repressors in order to promote transition of the hemogenic endothelium to HSCs [42,46].…”
Section: Discussionmentioning
confidence: 99%
“…Stable-transfection assays were performed as described previously (24). Briefly, 10 7 MS1 or SEND cells were electroporated at 220 V and 900 F in microcuvettes along with 10 g of the luciferase vector and 1 g of the pGK-Puro resistance vector.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen nuclei were subsequently pooled and lysed. ChIP assays were performed as previously described (24). Antibodies used in the study were H3K9ac (catalog number 06-599; Millipore); GATA2 (catalog number sc-9008x), SCL (catalog number sc12984X), Ets1 (catalog number sc350x), Ets2 (catalog number sc351x), and Elf1 (catalog number sc631X) (all from Santa Cruz); and Runx1 (catalog number ab23980), Fli1 (catalog number ab15289), and FoxC2 (catalog number ab5060) (all from Abcam) antibodies, and ChIP samples were quantified by using qPCR via Sybr green chemistry (Life Technologies) on a Stratagene Mx300p instrument (Agilent).…”
Section: Methodsmentioning
confidence: 99%
“…As we can see qualitatively from the topology of the network, outputs from multiple triad genes also activate smad6 transcription as well as runx1 transcription. The key to the subcircuit dynamics is that Smad6 is a negative regulator: thus while a Smad1/Runx complex positively regulates the triad genes, Smad6/Runx and Smad6/Smad1 complexes are targeted for degradation (Knezevic et al, 2011). Thus, as the triad picks up steam, Smad6 expression is accentuated, resulting in the eventual disappearance of both pSmad1 and Runx1.…”
Section: Hsc Specification In the Embryonic Agmmentioning
confidence: 99%